Label-free Capacitive Diagnostics: Exploiting Local Redox Probe State Occupancy - Lehr, Joshua; Bedatty Fernandes, Flavio C. [UNESP]; Bueno, Paulo Roberto [UNESP]; Davis, Jason J. (Amer Chemical Soc, 2014)
An electrode surface confined redox group contributes to a substantial potential-dependent interfacial charging that can be sensitively probed and frequency-resolved by impedance-derived capacitance spectroscopy. In utilizing the sensitivity of this charging fingerprint to redox group environment, one can seek to generate derived sensory configurations. Exemplified here through the generation of mixed molecular films comprising ferrocene and antibody receptors to two clinically important targets, the label-free methodology is able to report on human prostatic acid phosphatase (PAP), a tumor marker, with a limit of detection of 11 pM and C-reactive protein with a limit of detection of 28 pM. Both assays exhibit linear ranges encompassing those of clinical value.